ANALISIS BIOMEKANIKA GERAKAN SPIKE BOLA VOLI MENGGUNAKAN SOFTWARE KINOVEA DI MTS AL-FATH KLAMPIS BANGKALAN - Wajalla, Ashadu; Widodo, Haryo Mukti; Handayani, Heni Yuli (Fakultas Ilmu Keolahragaan Unimed, 2025)
In this modern era, the application of biomechanical analysis in sports has proven to be very effective in improving athlete performance. Spike is one of the determining techniques in volleyball that requires optimal body coordination, including in the initial phase. This study aims to analyze the effect of the number of initial steps on the results of the ball and the angle of the jump when doing a spike. The research method uses a qualitative research approach involving 15 students of MTS AL-FATH who were selected through purposive sampling. Data were obtained through video recording and analyzed using Kinovea software to measure the angle of the jump from the results of the ball hit. The results showed that the number of initial steps affected the angle of the jump and the effectiveness of the hit. Three to four initial steps resulted in a more optimal jump angle and a more accurate ball hit. The conclusion of this study is that increasing the number of initial steps can improve spike performance in volleyball. The implications of these findings can be used as a basis for compiling a more effective spike technique training program for athletes and coaches.